Penerapan Pembelajaran Kooperatif Tipe Picture and Picture untuk Meningkatkan Perkembangan Kognitif Anak Usia Dini di Kelompok Bermain - Tutupary, Rosmaryn (Jurnal Bimbingan dan Konseling Terapan, 2017)
The world of children is a world of play, and learning is done with or while playing that involves all the senses of the child. Paud teachers and parents need to look at the aspects of personality that exist in the development of children, including aspects of cognitive aspects, aspects of moral values, aspects of intelligence, motor aspects, social aspects of emotional. These five aspects may affect the thinking aspect of the child, and this is highly dependent on the ability of each individual. Therefore, children need to get good and proper stimulation to optimize aspects of its development. This study aims to determine the application of cooperative learning picture and picture type in improving early childhood cognitive development in KB Mawar FKIP Unpatti Ambon. This research is a Classroom Action Research. The subjects of this study were students aged 4-5 years KB Roses FKIP Unpatti Ambon which amounted to 10 people. Data collection techniques are observation and interview. This classroom action research procedure is carried out in two cycles, namely cycle I and cycle II. To know the result of student learning by using learning strategy with song on cognitive aspect conducted evaluation in the form of observation to cognitive aspect. Where indicators are performed by holding observations after completion of learning in each cycle at the end of the second meeting. The results showed that in the first cycle, there are still students who do not meet the criteria of the indicators conducted by the tutor, so it can be said as a weakness encountered in the implementation of the first cycle action, while in cycle II students are very active hear the teacher explanation. Very active in question is that students can follow the teacher's explanation well so that what is assigned can be done well. Thus it can be concluded that by using cooperative learning picture and picture type can develop early childhood cognitive in KB Mawar FKIP Unpatti Ambon.